Development and validity of mathematical learning assessment instruments based on multiple intelligence - Suryani, Helmiah; Kartowagiran, Badrun; Jailani, Jailani (Jurnal Penelitian dan Evaluasi Pendidikan, 2017)
This study was aimed to develop and produce an assessment instrument of mathematical learning results based on multiple intelligence. The methods in this study used Borg & Gall-Research and Development approach (Research & Development). The subject of research was 289 students. The results of research: (1) Result of Aiken Analysis showed 58 valid items were between 0,714 to 0,952. (2) Result of the Exploratory on factor analysis indicated the instrument consist of three factors i.e. mathematical logical intelligence-spatial intelligence-and linguistic intelligence. KMO value was 0.661 df 0.780 sig. 0.000 with valid category. This research succeeded to developing the assessment instrument of mathematical learning results based on multiple intelligence of second grade in elementary school with characteristics of logical intelligence of mathematics, spatial intelligence, and linguistic intelligence.